DIGITAL IDENTITY, DATAFICATION AND EPIDERMALISATION IN MAE LA REFUGEE CAMP - Madianou, Mirca; Hill, Charlotte (AoIR Selected Papers of Internet Research, 2026)
Biometric cash transfers are becoming ubiquitous in the aid sector driven by donor demands for audit and cost efficiencies and as humanitarian organisations turn to technological solutions to address complex logistical challenges. What is often overlooked is the perspective of refugees themselves. Drawing on a mixed-methods study including 80 interviews and participatory action research, our paper examines biometric cash transfers as exemplars of digital identity systems from the point of view of Karen refugees in Mae La camp in Thailand. Focusing on the introduction of an aid distribution system based on face recognition, our findings reveal that while digital identity programmes offer some advantages, there are significant concerns with their implementation. The new system raises both practical and ethical concerns, such as reduced rations, systematic errors, and power asymmetries. This paper argues that digital identity is not simply a form of identity provided in digital format: the conversion of human beings into data has significant consequences for recognition, dignity, privacy and freedom.